Strategies to promote evidence use for health programme improvement: learning from the experiences of embedded implementation research teams in Latin America and the Caribbean - N. Ilona Varallyay; Caitlin Kennedy; Sara C. Bennett; David H. Peters (BMC, 2022)
Abstract Background To achieve global health targets, innovative approaches are needed to strengthen the implementation of efficacious interventions. New approaches in implementation research that bring together health system decision-makers alongside researchers to collaboratively design, produce and apply research evidence are gaining traction. Embedded implementation research (EIR) approaches led by decision-maker principal investigators (DM PIs) appear promising in this regard. Our aim is to describe the strategies study teams employ in the post-research phase of EIR to promote evidence-informed programme or policy improvement. Methods We conducted a prospective, comparative case study of an EIR initiative in Bolivia, Colombia and Dominican Republic. Guided by a conceptual framework on EIR, we used semi-structured key informant interviews (n = 51) and document reviews (n = 20) to examine three decision-maker-led study teams ("cases"). Focusing on three processes (communication/dissemination, stakeholder engagement with evidence, integrating evidence in decision-making) and the main outcome (enacting improvements), we used thematic analysis to identify associated strategies and enabling or hindering factors. Results Across cases, we observed diverse strategies, shaped substantially by whether the DM PI was positioned to lead the response to study findings within their sphere of work. We found two primary change pathways: (1) DM PIs implement remedial measures directly, and (2) DM PIs seek to influence other stakeholders to respond to study findings. Throughout the post-research phase, EIR teams adapted research use strategies based on the evolving context. Conclusions EIR led by well-positioned DM PIs can facilitate impactful research translation efforts. We draw lessons around the importance of (1) understanding DM PI positionality, (2) ongoing assessment of the evolving context and stakeholders and (3) iterative adaptation to dynamic, uncertain circumstances. Findings may guide EIR practitioners in planning and conducting fit-for-purpose and context-sensitive strategies to advance the use of evidence for programme improvement.